USD 500 million Kazakhstan Sustainable Livestock Development Program for Results Project - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
World Bank invested USD 500 million in the Kazakhstan Sustainable Livestock Development Program for Results Project, informed by soil carbon monitoring methods advised by CCAFS and partners.